Clinical workflow and applicability of electrophysiological cardiovascular magnetic resonance-guided radiofrequency ablation of isthmus-dependent atrial flutter. (10th October 2018) - Paetsch, Ingo; Sommer, Philipp; Jahnke, Cosima; Hilbert, Sebastian; Loebe, Susanne; Schoene, Katharina; Oebel, Sabrina; Krueger, Sascha; Weiss, Steffen; Smink, Jouke; Lloyd, Tom; Hindricks, Gerhard
Abstract: Aims: To determine safety and efficacy of electrophysiological cardiovascular magnetic resonance (EP-CMR)-guided radiofrequency (RF) ablation in patients with typical right atrial flutter in a routine clinical setting. Methods and results: Thirty patients with typical right atrial flutter underwent clinically indicated EP-CMR-guided cavotricuspid isthmus ablation. EP-CMR protocols included pre- and post-ablation CMR imaging (whole heart, T2-weighted, and early-/late-gadolinium enhancement) together with electroanatomic mapping of the right atrium. Coronary sinus cannulation time and total ablation procedure duration were used as performance measures to determine the learning experience of the EP-CMR interventionalist and for comparison with conventional, fluoroscopy-guided atrial flutter ablation. Procedural safety and success rates were evaluated at 1 week and 3 months follow-up. Safety and success rates of EP-CMR were similar to conventional flutter ablations (primary success rate, 93% vs. 100%; recurrence rate, 0% vs. 3%, respectively). EP-CMR procedure duration indicated a learning experience (first vs. last six patients, 54.2 ± 23.1 vs. 29.7 ± 20.0 min) and the minimum number of procedures needed to achieve a level of competency was n  = 12. An isthmus angle <110° and the presence of pouch-like isthmus anatomy were indicative of significantly prolonged EP-CMR procedure duration. CMR-defined ablation lesion size was not associated with total RF-ablation time or RF-induced maximum temperature. Conclusion: In a routine clinical setting, EP-CMR demonstrated its safety and high efficacy for the treatment of typical right atrial flutter with performance and outcome measures similar to conventional, fluoroscopy-guided flutter ablation. Hence, EP-CMR represents a valid alternative to conventional right atrial flutter ablation.